Regenerasi Petani Melalui Peningkatan Kapasitas Pemuda dalam Program SaUng TaMu - Kholifah, Sisca Noor; Nurfajriah, Siti Robiah; Kamila Zahra Salsabila,; Sylvia Nika Puspitasari, (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2024)
The decrease in the number of agricultural laborers has caused concern regarding the regeneration of farmers in Genteng Village presently. A series of efforts are required to enhance the interest of rural youth in agriculture, one of which is through the SaUng TaMu program organized by the PPK Ormawa of the Plant Clinic, utilizing a Participatory Active Learning approach. The outcomes of these activities reveal that the PPK Plant Clinic Team from Unpad has established the SaUng TaMu youth agro-complex group, culminating in the development of a Nursery Green House and individual business ideas for the supported community members. To equip the beneficiary group, the PPK Plant Clinic Team conducted various training sessions and field trips aimed at supporting the implementation and sustainability of the program. Based on the provided questionnaires, there was a sequential increase in scores across each training session, registering percentages of 11.11%, 15.7%, 58.73%, and 122.22% respectively.